Promoting Free Writing Skill in ELT Classroom: An Exploratory Action Research Study - G.C., Yam Bahadur (An ENDEAVOUR: Journal of Academia and Research, 2026)
This exploratory action research (EAR) study investigated the difficulties faced by class ten students in free writing in English and implemented interventions to enhance their writing skills. The EAR study was conducted to the class 10 students of Shree Jeevan Jyoti English Boarding School, Syangja. The study involved 23 students and used both quantitative and qualitative data through close-ended and open-ended questionnaires, classroom observations, reflective journals and analysis of students’ writing samples. The exploration phase revealed that students lacked confidence, hesitated to write, relied on guidebooks and faced challenges in vocabulary, grammar and organization of ideas. Various interventions including brainstorming activities, vocabulary journals, model writing, regular free writing practice, and peer feedback were implemented over four weeks. Post-intervention findings indicated significant improvements in students’ fluency, coherence, vocabulary use, confidence and originality in writing. The study shows that the effectiveness of EAR as a reflective, practice- based framework for addressing classroom writing issues in Nepalese EFL contexts.